2020
DOI: 10.1007/s13238-019-00687-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the pattern recognition receptor NOD1 augments colon cancer metastasis

Abstract: While emerging data suggest nucleotide oligomerization domain receptor 1 (NOD1), a cytoplasmic pattern recognition receptor, may play an important and complementary role in the immune response to bacterial infection, its role in cancer metastasis is entirely unknown. Hence, we sought to determine the effects of NOD1 on metastasis. NOD1 expression in paired human primary colon cancer, human and murine colon cancer cells were determined using immunohistochemistry and immunoblotting (WB). Clinical significance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…NOD1 and NOD2 are sensors of different bacterial peptidoglycan components. It has been previously shown that the activation of NOD1 promotes colon cancer metastases ( Jiang et al, 2020 ); inhibition of RIPK2 can delay NOD signaling to decrease the production of inflammatory cytokine ( Nachbur et al, 2015 ), so RIPK2 could regulate the NOD signaling to control the occurrence and development of inflammation-related tumors. Collectively, these genes were predicted based on the neighborhood, co-expression, database, experiment data, co-occurrence, and text mining.…”
Section: Discussionmentioning
confidence: 99%
“…NOD1 and NOD2 are sensors of different bacterial peptidoglycan components. It has been previously shown that the activation of NOD1 promotes colon cancer metastases ( Jiang et al, 2020 ); inhibition of RIPK2 can delay NOD signaling to decrease the production of inflammatory cytokine ( Nachbur et al, 2015 ), so RIPK2 could regulate the NOD signaling to control the occurrence and development of inflammation-related tumors. Collectively, these genes were predicted based on the neighborhood, co-expression, database, experiment data, co-occurrence, and text mining.…”
Section: Discussionmentioning
confidence: 99%
“…The potential contribution of Nod1 signaling in mediating the immunosuppressive activity of intra-tumoral myeloid cells is particularly interesting, as NOD1 expression is significantly elevated in human CRC tissue when compared to controls and increases with progressing stages of CRC (Liu et al, 2015b). Moreover, Nod1 activation has recently been implicated with increased CRC metastasis (Jiang et al, 2020), which further supports the concept that MPs can potentiate CRC by modulating the activity of intra-tumoral myeloid cells.…”
Section: Introductionmentioning
confidence: 59%
“…The NOD1–cancer axis has been widely confirmed and it is quite relevant due to the high morbidity and mortality associated with these diseases [ 25 , 39 , 54 , 77 , 78 , 79 , 80 , 81 , 82 ]. For instance, a recent study has shown that activated NOD1 leads to the progression of colorectal carcinogenesis by modulating the immunosuppressive functions of tumor-infiltrating leukocytes via arginase-1 activity [ 77 ].…”
Section: Nod1-related Diseases and Nutrients: The Potential Benefit Of Immunonutrition Approachesmentioning
confidence: 99%
“…For instance, a recent study has shown that activated NOD1 leads to the progression of colorectal carcinogenesis by modulating the immunosuppressive functions of tumor-infiltrating leukocytes via arginase-1 activity [ 77 ]. Other previous studies have also linked NOD1 activities to colon cancer and metastasis [ 79 , 82 ] and carcinogenic responses to Helicobacter pylori pathogen [ 80 ]. Given the high impact of nutrition on the gastrointestinal tract and the microbiota content (also closely linked to NOD1) and the information provided by these studies, new immunonutrition strategies are required.…”
Section: Nod1-related Diseases and Nutrients: The Potential Benefit Of Immunonutrition Approachesmentioning
confidence: 99%
See 1 more Smart Citation